Policy Implementation of the Merdeka Curriculum in an Islamic Junior High School: A Mixed-Methods Study at SMP At-Taqwa 10 Bekasi - Riyan Nuryadin; Mirwan; Faer Rifaie, Muhammad Mukrim; Hamdani, Mohammad Rusli; Zaqiah, Qiqi Yuliati (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2026)
Curriculum reform policies often assume that schools are able to translate national directives into coherent classroom practice, yet empirical evidence shows that implementation is frequently uneven and shaped by local institutional contexts. This study examines how the Merdeka Curriculum is enacted as a public education policy in an Islamic junior high school, addressing the limited policy-focused literature on curriculum enactment in value-based school settings. Using a sequential explanatory mixed-methods design, the study analyzes teachers’ perceptions and practices to capture both broad implementation patterns and their contextual explanations at the school level. The findings reveal a selective and asymmetrical pattern of policy enactment. Components aligned with institutional values, such as religious school culture, leadership support, and character education, are enacted more strongly, while pedagogically demanding elements, particularly differentiated instruction, remain a persistent implementation bottleneck. The enactment of Pancasila Student Profile Projects (P5) emerges as a key mechanism of policy mediation, as national policy objectives are translated into religious routines and social-service activities that resonate with the school’s Islamic identity. However, the study also finds that authentic assessment practices, although positively perceived, are constrained by uneven rubric quality and limited documentation of learning evidence. The study concludes that religious school culture can function as an enabling infrastructure for curriculum policy enactment, but without sustained pedagogical support, especially in differentiation and assessment literacy, policy autonomy risks producing symbolic rather than substantive implementation.